Titanium a technical guide - Donachie, Matthew J. (ASM International, 2000)
Designed to support the need of engineering, management, and other professionals for information on titanium by providing an overview of the major topics, this book provides a concise summary of the most useful information required to understanding titanium and its alloys. The author provides a review of the significant features of the metallurgy and application of titanium and its alloys. All technical aspects of the use of titanium are covered, with sufficient metals property data for most users. Because of its unique density, corrosion resistance, and relative strength advantages over competing materials such as aluminum, steels, and superalloys, titanium has found a niche in many industries. Much of this use has occurred through military research and subsequent applications in aircraft or gas turbine engines, although more recent use features replacement joints, golf clubs, and bicycles.
Keywords: Titanium.; Titanium alloys.; elektronické knihy; electronic books